2019
DOI: 10.4236/ojbm.2019.74110
|View full text |Cite
|
Sign up to set email alerts
|

Factors Contributing to the Success of Ethnic Restaurant Businesses in Canada

Abstract: Due to the small size of their businesses, small business owners often face a high failure rate. Within the first 7 years since opening, more than half of small businesses seek to close its operation. The author of this qualitative multi-case study examines the factors contributing to the success of small ethnic restaurants owners to remain operable beyond 7 years. The owners of three small ethnic restaurants that have been operating for more than 7 years in Metro Vancouver, British Columbia, Canada were selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…However, previous analysis of place-making efforts, including downtown revitalization, has been sparse due to the "fuzzy" nature (see Markusen, 2013) of measuring concepts such as vibrancy and economic vitality. Le and Needham (2019) observed the business outcomes of small restaurants within a given community and found that their survival was aided by having competitive locations with higher levels of foot traffic, proximity to other anchors (such as a university or transit station), and places where civic activities and cultural events are held. In addition, Credit and Mack (2019) identified a positive association between the use of "design-based place-making initiatives" and business performance, measured as sales volume per employee.…”
Section: Proximity To a Downtownmentioning
confidence: 99%
“…However, previous analysis of place-making efforts, including downtown revitalization, has been sparse due to the "fuzzy" nature (see Markusen, 2013) of measuring concepts such as vibrancy and economic vitality. Le and Needham (2019) observed the business outcomes of small restaurants within a given community and found that their survival was aided by having competitive locations with higher levels of foot traffic, proximity to other anchors (such as a university or transit station), and places where civic activities and cultural events are held. In addition, Credit and Mack (2019) identified a positive association between the use of "design-based place-making initiatives" and business performance, measured as sales volume per employee.…”
Section: Proximity To a Downtownmentioning
confidence: 99%
“…Research has shown that owner’s personality, attitude, and competency (business acumen) have a substantial effect on restaurant performance (Le & Needham, 2019). Successful restaurant entrepreneurs are hardworking, ethical, and deliver exceptional service (Chen & Elston, 2013).…”
Section: The Restaurant Industrymentioning
confidence: 99%